In vivo and in silico studies of the effects of oil extracted from Cannabis sativa L. seeds on healing of burned skin wounds in rats - Bouarfa, Mouna; Chebaibi, Mohamed; Ez-Zahra Amrati, Fatima; Souirti, Zouhair; Saghrouchni, Hamza; El atki, Yassine; Bekkouche, Khalid; Mourabiti, Hajar; Bari, Amina; Giesy, John P.; Mohany, Mohamed; Al-Rejaie, Salim S.; et al. (Frontiers in Chemistry, 2024)
This study investigates the potential effects of cannabis seed oil (CSO) on the wound healing process. Potential activity of CSO in treating skin wounds was assessed in an animal model. A total of 18 male albino Wistar rats weighing between 200-250g were used in the study, divided into three groups: the untreated negative control group, the group treated with the reference drug SSD (0.01g/mL), and the group treated topically with CSO (0.962g/mL). The initial wound diameter for all groups was 1 cm. Simultaneously, an in-silico study of anti-inflammatory effects of phytoconstituents against Cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2) were conducted using Maestro 11.5. CSO and SSD treatments led to a significant reduction (P < 0.05) in the size of burned skin wounds by day 5, with contraction rates of 53.95% and 45.94%, respectively, compared to the untreated negative control group. By day 15, wounds treated with CSO and SSD had nearly healed, showing contraction rates of 98.8% and 98.15%, respectively.By day 20, the wounds treated with CSO had fully healed (100%), while those treated with SSD had almost completely healed, with a contraction rate of 98.97%. Histological examination showed granulated tissue developing over the wounds treated with CSO, where with proliferation of neo-blood vessels, fibroblasts, and collagen fibers. Results of in silico studies showed that Arachidic Acid, γ-linolenic acid, and Linolenic Acid were post potent and efficacious at inhibiting COX-1 and COX-2. Serum biochemical parameters for both liver and kidney function revealed no significant (p > 0.05) changes in rats treated with CSO. However, a significant (p < 0.01) increase in ALAT level was observed in rats treated with SSD. While our findings reveal promising outcomes, it is essential to indicate the limitations inherent in our research. Firstly, the sample size utilized may impact the generalizability of our findings to larger samples. Additionally, although our investigation provides encouraging information into the healing effects of CSO, the elucidation of its mechanism of action remains limited in detail.Future research endeavors should aim to expand upon these findings by exploring the molecular pathways and signaling processes involved in CSO's pharmacological effects.